2020
DOI: 10.1093/ofid/ofaa439.1688
|View full text |Cite
|
Sign up to set email alerts
|

1507. Clinical Characteristics of Common Respiratory Viruses Detected in Infants Across Different Clinical Settings

Abstract: Background Viral acute respiratory infections (ARI) continues to be a significant cause of healthcare visits in young children. We evaluated the clinical presentation and disease severity of common respiratory viruses associated with medically attended ARI in infants. Methods We conducted a prospective viral surveillance study in Davidson County, TN. Infants under one year with fever and/or respiratory symptoms were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Twenty‐five studies reported on RSV S&S in the target pediatric population. In addition, 13 studies reported symptom duration, 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 including nine studies that also presented RSV S&S. Hospital LOS was extracted from 13 of the included studies in this review. 19 , 21 , 25 , 26 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty‐five studies reported on RSV S&S in the target pediatric population. In addition, 13 studies reported symptom duration, 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 including nine studies that also presented RSV S&S. Hospital LOS was extracted from 13 of the included studies in this review. 19 , 21 , 25 , 26 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…Studies on S&S of RSV in the pediatric population (25 studies) took place in both community and clinical settings, and S&S were reported by both caregivers (six studies) 19 , 20 , 21 , 39 , 40 , 41 and clinicians (22 studies) 19 , 20 , 21 , 26 , 27 , 28 , 29 , 34 , 35 , 37 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ; we analyzed and present these two sets separately. In addition, two publications presented clinician‐reported S&S in the intensive care unit (ICU).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations